A Liaison Model Approach to Research Skills Instruction In Light of the New ACRL Information Literacy Framework - Djokic, Mirela; Kargut, Sigrid (Qualitative and Quantitative Methods in Libraries; Vol 6 No 2 (2017): June 2017 Issue, 2019)
The objective of the presentation is to discuss the impact of the new Information Literacy Framework Threshold Concepts on the delivery of library research skills instruction at Kwantlen Polytechnic University (KPU). In 2011 KPU Library had adopted the Instruction Core Principles of the previous Information Literacy Standards and our teaching methodology and lesson plans were then based on these principles. With the adoption of the New Framework in 2015, KPU librarians are currently reviewing and assessing library instruction programs, while at the same time piloting new Information Literacy sessions. The new Framework seeks to move what librarians teach from the "how" of information literacy skills to the "why" of information creation and use. Threshold concepts enable students to experience possibilities of higher critical thinking within disciplines. This presentation will showcase how librarians at KPU are adjusting their teaching practices to conform to the new Framework threshold concepts, and are implementing sequential, integrated information literacy programs based on the liaison model. Methods to assess student learning are also being presented.